2012
DOI: 10.1038/nn.3139
|View full text |Cite
|
Sign up to set email alerts
|

Drosha regulates neurogenesis by controlling Neurogenin 2 expression independent of microRNAs

Abstract: Temporal regulation of embryonic neurogenesis is controlled by hypostable transcription factors. The mechanism of the process is unclear. Here we show that the RNase III Drosha and DGCR8 (also known as Pasha), key components of the microRNA (miRNA) microprocessor, have important functions in mouse neurogenesis. Loss of microprocessor in forebrain neural progenitors resulted in a loss of stem cell character and precocious differentiation whereas Dicer deficiency did not. Drosha negatively regulated expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 56 publications
5
129
2
1
Order By: Relevance
“…S1). qRT-PCR analysis revealed that, instead of an increase of Neurog2 transcripts as reported in Drosha -/-NPCs [25], Neurog2 expression is significantly downregulated in Dgcr8 -/-NSCs (Fig. 1D).…”
Section: Dgcr8supporting
confidence: 50%
See 2 more Smart Citations
“…S1). qRT-PCR analysis revealed that, instead of an increase of Neurog2 transcripts as reported in Drosha -/-NPCs [25], Neurog2 expression is significantly downregulated in Dgcr8 -/-NSCs (Fig. 1D).…”
Section: Dgcr8supporting
confidence: 50%
“…Because it has been implicated that Drosha -/-NPCs would quickly differentiate into neurons in embryonic brain due to accumulation of Neurog2 transcripts [25], we examined whether Dgcr8 -/-NSCs are similarly defective in self-renewal by long term in vitro passaging. We found that Dgcr8 -/-NSCs can be stably cultured for at least 20 passages without noticeable changes in cell morphology or stem cell marker expression ( Supplementary Fig.…”
Section: Dgcr8mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a well recognized role of miRNAs is to function as a fail-safe mechanism to eliminate the effect of baseline levels of transcription (81,83,84). Second, it is also possible that DGCR8 itself directly destabilizes certain mRNAs (85), and such targets would be derepressed in Dgcr8 cKO mutants. Third, denervation-associated genes may be up-regulated indirectly due to the loss of axons or the receipt of axonal signals.…”
Section: Loss Of Dgcr8 Dysregulates the Balance Between Positive And mentioning
confidence: 99%
“…In the early stages of mammalian forebrain neurogenesis, the Microprocessor complex directly binds to and destabilizes the Neurog2 mRNA. Ablating DGCR8 in this system stabilizes the expression of such proneural genes and leads to precocious differentiation that is not seen in Dicer1 knockouts (85). Indeed, DICER1-dependent and DGCR8-independent non-canonical miRNAs, such as endogenous shRNA, siRNA, mirtrons, and H/ACA small nucleolar RNA-derived small RNA, have also been shown to underpin phenotypes that are more severe in Dicer1 knockouts than in Dgcr8 knockouts (88 -90).…”
Section: Loss Of Dgcr8 Dysregulates the Balance Between Positive And mentioning
confidence: 99%